2021
DOI: 10.1016/j.jare.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tear proteomic and neuromediator profiles changes between small incision lenticule extraction (SMILE) and femtosecond laser-assisted in-situ keratomileusis (LASIK)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Additionally, B lymphocytes secrete Igs, also known as antibodies that mediate the effector phase of humoral immunity [54]. Recently, some research showed significant changes in Igs in tear protein profiles in specific diseases like diabetic retinopathy, primary open-angle glaucoma, and postrefractive surgery [55,56]. In our study, we found a decrease in Ig heavy variable 5-10-1 in the iERM group.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, B lymphocytes secrete Igs, also known as antibodies that mediate the effector phase of humoral immunity [54]. Recently, some research showed significant changes in Igs in tear protein profiles in specific diseases like diabetic retinopathy, primary open-angle glaucoma, and postrefractive surgery [55,56]. In our study, we found a decrease in Ig heavy variable 5-10-1 in the iERM group.…”
Section: Discussionsupporting
confidence: 61%
“…Quantitative tear proteomic analysis was performed as previously described (25). The Schirmer strips were cut into small pieces, and 100 μl lysis buffer was added and mixed in a Thermomixer for 1.5 hours at 20 ºC.…”
Section: Tear Proteomic Analysismentioning
confidence: 99%
“…[ 37 38 ] Both RCLE and LASIK induce a transient worsening in dry eye parameters, but there is evidence showing that RCLE has a less negative impact on ocular surface parameters and allows for an earlier recovery. [ 37 39 ] Analyzing ocular surface changes in 15 patients post SMILE and 32 post FS-LASIK, Gao et al . found lower fluorescein staining scores after 1 week, longer tear breakup times after 1 and 3 months, higher central corneal sensitivity at 1 week, 1 and 3 months as well as lower levels and a faster decrease of interleukin-6 and nerve growth factor in tears following SMILE compared to FS-LASIK.…”
Section: Advantages Of Refractive Corneal Lenticule Extractionmentioning
confidence: 99%